Penggunaan kombinasi adsorben sebagai media filtrasi dalam menurunkan kadar fosfat dan amonia air limbah laundry - Septiany Christin Palilingan; Meity Pungus; Farly Tumimomor (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Wastewater of detergent residual that comes from the washing process (laundry) has the potential to pollute environmental sustainability such as rivers and soil if it is thrown away in large volumes without any prior processing. Easy and inexpensive methods for processing laundry wastewater for household-scale have been carried out and proven to reduce levels of pollutants contained in laundry wastewater such as phosphate and ammonia. This study aims to determine the effect of the use of filtration media using a combination of activated charcoal adsorbent, zeolite, silica sand, anthracite and ferolite in reducing phosphate and ammonia levels in laundry wastewater. Based on the results of laboratory tests on the parameters of phosphate and ammonia test, it was found that after the filtration process, there was a decrease in phosphate and ammonia levels in the samples of laundry wastewater by 83.3% and 63.6% respectively. Thus, from the research data, it can be concluded that the filtration media in the form of a combination of adsorbents used in this study proved to be able to reduce phosphate and ammonia levels in samples of laundry wastewater.